Oxygen consumption and nutrient fluxes in coastal marine sediments off the Mejerda River delta (Gulf of Tunis) - HELALI, M. A.; ZAABOUB, N.; OUESLATI, W.; ADDED, A.; ALEYA, L. (Mediterranean Marine Science, 2015)
The authors studied benthic flux of oxygen, alkalinity, and nutrients in situ at three points in the Mejerda River Delta at depths of 10m, 20m and 40m in March and August 2012. Three sedimentary cores were simultaneously drilled at the same locations to determine the diffusive flux of NO2-, NO3-, NH4+ and PO43- and to estimate diagenetic mechanisms occurring below the sediment-water interface. Photosynthesis was not sufficiently high during the day, and the oxygen consumption at sediment-water interface was about 1.7 to 10mmol/m²/day, essentially controlled by the degradation of organic matter and oxidation of reduced elements. Nitrate contents are relatively high in the sediment (above 140μM for NO3-)and their production is not always in conformity with the general scheme of early diagenesis, moreover, benthic flux between water and sediment are not clearly established. The diffusive flux of NH4+ and PO43- are always directed to the water column, at averages of 1.27μmol/m²/day for PO43- and 96.5μmol/m²/day for NH4+, complying with those measured by benthic chambers, but representing less than 30% of benthic fluxes for NH4+ and less than 5% for PO43-.